Socio-Economic Issues of Development Plan from Indigenous Peoples' Point of View - Bhandari, Uma (Socio-Economic Development Panorama, 2008)
Development is a great issue and challenge or the people of the third world countries. Although, the practice of planned development in many countries started only after Second World War, the issue of the effect of it to the life of poor society or country is now under question. Development activists argue that rural people and the people of certain class, caste, sex of territory of Nepal still remains deprived despite the implementation of the planned development activities. It is revealed that the poverty rate of Nepal is still 31 percent on an average and it is higher among Dalits and Indigenous groups of people. So, social activities, political, and development activist have shown great concern on the drawbacks of the development activities implemented so far. Considering these views, This article focuses on the hindering socio-economic issues of underdevelopment of rural people of Nepal. This article has critically raised questions on the relevancy of current development practices and has offered some alternatives to be undertaken as a way forward for the Indigenous people of Nepal. Socio-Economic Development Panorama, Vol. 1, No. 2(2007) pp. 101-110